INTERNATIONAL TECHNICAL AID IN POST-CONFLICT RECOVERY: LESSONS FROM GLOBAL PRACTICES FOR DE-OCCUPIED AREAS - Viktoriia Zalizniuk; Anton Plaksun (Baltic Journal of Economic Studies)
The article presents a study of theoretical, methodological, and applied approaches to the engagement of international technical assistance (ITA) in post-conflict recovery processes, with a particular focus on its potential application in the reconstruction of de-occupied territories in Ukraine. The paper substantiates the necessity of integrating ITA into the national framework for reconstruction, reintegration, and stabilization under the conditions of martial law and systemic transformation. ITA is conceptualized as a strategic resource that encompasses financial, technical, expert, and institutional support from international donors aimed at the implementation of long-term sustainable development programs. The article provides a structural analysis of the forms of international technical assistance, the mechanisms of its provision, and institutional coordination, particularly in the context of cooperation between governments, intergovernmental organizations, financial institutions, and civil society actors. Key criteria for evaluating the effectiveness of ITA are outlined, along with methods of monitoring, auditing, and risk management. Special attention is paid to transparency and accountability issues in the implementation of technical support projects in countries with post-conflict status. Within the empirical component of the research, international experience in post-conflict recovery and reintegration is examined using the cases of Kosovo, Iraq, Afghanistan, Georgia, and Croatia. A comparative analysis of ITA models in these states is carried out, highlighting institutional successes, shortcomings, and adaptable practices relevant to the Ukrainian context. The article emphasizes the importance of leveraging such experience not only for infrastructural reconstruction but also for strengthening public administration, security, the rule of law, and public trust in the reintegration of de-occupied areas. The scientific novelty of the research lies in the systematic generalization and critical rethinking of foreign experience in international technical assistance within post-conflict recovery, assessed through the lens of its applicability to modern Ukraine. For the first time, a comparative analysis is conducted of ITA models in countries with varying degrees of de-occupation (full, partial, absent), enabling the development of a typology of approaches to stabilization, reintegration, and institutional recovery of liberated territories. Thus, we can observe in the article the following. Subject of the study. This research addresses the conceptual and institutional foundations of international technical assistance (ITA) within the context of post-conflict recovery. It focuses on identifying and analysing mechanisms for the application of ITA in the processes of reconstruction, reintegration, and stabilization of de-occupied territories, with particular emphasis on the Ukrainian case. Methodology. The methodological framework of the study combines comparative analysis, institutional diagnostics, and the examination of selected international case studies. The empirical component relies on the analysis of post-conflict recovery practices in Kosovo, Iraq, Afghanistan, Georgia, and Croatia. The study applies qualitative content analysis and institutional comparison, supported by an assessment of aid effectiveness, monitoring instruments, and governance models. Purpose of the Study. The purpose of this research is to critically examine the role of international technical assistance in post-conflict settings and to assess the relevance of global experience to the Ukrainian context. The study aims to propose an analytical framework for integrating ITA into national recovery policy, with particular attention to its potential for enhancing institutional resilience and promoting sustainable reintegration. Conclusions. The study demonstrates that international technical assistance can function as a key component in the recovery and stabilization of territories affected by conflict, provided it is coherently embedded in national strategic planning. The findings suggest that the effectiveness of ITA depends on the alignment between donor approaches and local needs, institutional capacity, and mechanisms of coordination. Based on the comparative analysis, the research develops a typology of ITA application in countries with differing post-conflict trajectories, offering applicable insights for the reconstruction of Ukraine’s de-occupied areas.